Reliability of different smartphones measuring the hallux valgus parameters in a new rapid method: a follow-up study - Wang, Lin; Zhang, Chao; Liang, Hao; Zhang, Jun; Zhong, Weiyang; Zhao, Zenghui; Huang, Tianji; Luo, Xiaoji (BMC musculoskeletal disorders, 2022)
Objective This study aimed to further compare the abilities to measure hallux valgus parameters in different smartphones using the intrinsic photograph-editing function. Methods We retrospectively reviewed 61 patients (100 feet) of hallux valgus without medical or surgical interventions at our department. The radiographic parameters were assessed and measured via the Picture archiving and communication systems (PACS), iPhone, and Android. The accuracy, reliability, and the time-taken were compared and analyzed between each two methods. Results The mean value of measured hallux valgus parameters were as follow: hallux valgus angle (HVA): 33.71 ± 7.25°; the first and second intermetatarsal angle (IMA): 12.84 ± 3.62° in PACS; HVA: 33.59 ± 7.18° and IMA: 12.80 ± 3.65° in Android; HVA: 33.63 ± 7.23° and IMA: 12.87 ± 3.60° in iPhone. No significant difference was found among the average results measured by PACS, Android and iPhone ( F = 0.008, P = 0.992 in HVA; F = 0.009, P = 0.991 in IMA). For measurements by PACS, Android smartphone, and iPhone, the variability of HVA ( F = 0.061, P = 1.000) and IMA ( F = 0.133, P = 1.000) was similar. The intraclass correlation coefficients (ICCs) of the mean results of four times measurements of HVA and IMA as follows: PACS vs Android: 0.995 (0.993–0.997) and 0.982 (0.973–0.988); PACS vs iPhone:0.997 (0.995–0.998) and 0.974 (0.962–0.982); Android vs iPhone:0.997 (0.995–0.998) and 0.981 (0.971–0.987). The interobserver and intraobserver reliability was very good for Android smartphones and iPhone in measuring hallux valgus parameters. The mean time of measurement by PACS, Android smartphone, and iPhone were 25.34 ± 1.18 s, 20.10 ± 0.92 s, and 19.92 ± 0.99 s respectively. The measurement time of smartphones is significantly faster than that of PACS by about 5 seconds ( P = 0.000). The measurement time of iPhone was slightly faster than that of Android smartphone, while no significant difference was found ( P = 0.24). Conclusion It is more convenient and faster to use smartphones when compared with PACS, at the same level of accuracy. Furthermore, the abilities of different smartphone platforms are proven to be of no significant difference.